Ceserani & Kinton's The Theory of Catering - Foskett, David, 1951-; Ceserani, Victor (London : Hodder Arnold, 2007)
Aimed at catering students this book covers all key aspects of modern catering syllabuses, presenting the theory necessary for professional catering practice. Specific areas have been updated in this edition, and a larger colour section is included.
Previous ed.: 2003.
Formerly CIP.
Includes bibliographical references and index.
Keywords: Caterers and catering; Food industry and trade; Hospitality industry; Food service management